The Chaplin Mutuals. Volume three [videorecording (DVD)] - Chaplin, Charlie, 1889-1977; Bergman, Henry, 1870-1946; Purviance, Edna, 1896-1958; Campbell, Eric; Austin, Albert (Image Entertainment, 1997)
Four 2-reel comedies by filmmaker Charlie Chaplin, originally produced as part of his 12-film contract with the Mutual Film Corporation.